تطور خط النسخ من القرن الثالث حتى القرن السابع الهجري - Moch Wahib Dariyadi; Nurul Murtadho (Journal of Calligraphy, 2021)
F rom each type of Arabic script, long independent stages were drawn from their emergence to the stages of their completion. These lines were able to gradually develop from their primitive and incomplete forms to their complete or more perfect status over many successive centuries until they reached it today. Likewise, the naskh script developed gradually, successively, as did other Arabic scripts. This paper offers to describe how the Naskh script developed from the third to the seventh century AH. The results of this research is (1) The forms of letters, the Naskh script, were in the stage of script development in the third and fourth centuries influenced by the line of inquisitor. In the fourth and sixth centuries it was affected by the Rayhani line, and in the seventh century it was affected by the third line, And (2) The naskhi script in early Islam was used among people other than official writings until the minister, Abu Ali Muhammad bin Muqla, produced a great improvement in the aforementioned calligraphy and introduced it to writing Qur’ans and writing collections, since the third century.